EXPERIENCE OF WORKING OF METHODICAL HEATING FURNACES OF ROLLING PRODUCTION AT RUP “BMZ” - I. V. Kotov (Литьë и металлургия, 2004)
The experience of exploitation of continuous heating furnaces, established in section rolling workshops of RUP BMZ, the peculiarities of the construction and decisions, which allowed to reach stable and economical operation of units, is considered in the article